Intelligent nature-based solutions in the 1st smart sustainable Brazilian City: Insights and lessons learned - Bressane, Adriano [UNESP]; Loureiro, Anna Isabel Silva [UNESP]; Medeiros, Líliam César de Castro [UNESP]; Moruzzi, Rodrigo [UNESP]; Formiga, Jorge Kennety Silva [UNESP]; Negri, Rogério Galante [UNESP]; Saraiva, Antônio Carlos Varela [UNESP] (Elsevier, 2024)
As urbanization intensifies worldwide, the need for sustainable urban development becomes increasingly critical. This study introduces a novel approach, the Intelligent Nature-based Solutions (INbS), which encompasses the integration of nature-based approaches with intelligent systems. Drawing upon empirical context within the framework of the 1st Smart Sustainable Brazilian City, we engage in a perspective on the insights gained and lessons learned, offering strategic recommendations for guiding future INbS initiatives. It underscores the paramount significance of interdisciplinary collaboration, stakeholder engagement, and adaptive management strategies for the seamless amalgamation of these two domains, the technology and ecology. The study also probes into emerging challenges like the need for scalable, replicable models, ethical issues in data-driven decision-making, and the long-term effectiveness of INbS. By delving into these intricacies, this research seeks to contribute to a more profound comprehension of the potential and limitations inherent in the INbS within urban settings, particularly in emerging economies like Brazil.
Keywords: Intelligent systems; Nature-based solutions; Smart cities; Urban sustainability